2006
DOI: 10.1300/j052v25n03_08
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Hearing Loss, Methylmalonic Acid, and Vitamin B 12 Status in Older Adults

Abstract: Hearing loss has been associated with poor vitamin B12 status in some, but not all studies. This study examined a possible relationship between age-related hearing loss and poor B12 status in 93 older adults using different indices of B12 status. Hearing loss was defined as pure-tone average threshold > 25 decibel hearing level. Participants with methylmalonic acid (MMA) > 271 nmol/L at baseline received 1,000 g/d, and those with MMA < or = 271 nmol/L were randomly assigned to receive 0, 25, or 100 microg/d of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 32 publications
2
17
0
1
Order By: Relevance
“…Moreover, vitamin B 12 deficiency was associated with poor cognition in this study (77) and confirmed in a subsequent study (79). Vitamin B 12 deficiency was associated with several metabolic abnormalities (80) and with hearing loss (81), suggesting that vitamin B 12 deficiency may be a modifiable risk factor for hearing loss.…”
Section: Webinar On Food Insecurity In Older Georgianssupporting
confidence: 79%
“…Moreover, vitamin B 12 deficiency was associated with poor cognition in this study (77) and confirmed in a subsequent study (79). Vitamin B 12 deficiency was associated with several metabolic abnormalities (80) and with hearing loss (81), suggesting that vitamin B 12 deficiency may be a modifiable risk factor for hearing loss.…”
Section: Webinar On Food Insecurity In Older Georgianssupporting
confidence: 79%
“…Profile 2 may include individuals with an often genetic TC I deficiency, the frequency of which may be higher than that of pernicious anemia, and in whom serum vitamin B-12 is low but MMA and tHcy are not abnormal (39) or individuals who lack the common fucosyltransferase polymorphism associated with higher vitamin B-12 concentrations (43). Given the high proportion of younger women in profile 2, many of the low vitamin B-12 concentrations may have been affected by hormonal factors unrelated to functional vitamin B-12 status.…”
Section: Discussionmentioning
confidence: 99%
“…For this analysis, we added an additional cutoff of .296 pmol/L (.400 pg/mL) to the original Stabler et al criteria (30). We classified elevated MMA using 2 concentrations: .376 nmol/L (31)(32)(33)(34)(35) and .271 nmol/L (24,28,32,(36)(37)(38)(39). We also examined 4 categories of MMA based on the above cutoffs (.376 and .271 nmol/L) and .210 nmol/L (14,23,40,41).…”
Section: Biochemical Methodsmentioning
confidence: 99%
“…In contrast, Berner et al ( 2000 ) failed to demonstrate any association between hearing level and vitamin B 12 or folic acid in 91 elderly subjects. A poor vitamin B 12 status was also evident in 93 older adults with hearing loss (Park et al, 2006 ) but short-term dietary supplementation with vitamin B 12 did not affect their hearing.…”
Section: Protection From Cochlear Pathology and Pathophysiologymentioning
confidence: 99%